Electrical muscle stimulation (EMS) training of the hamstrings - Lategan, L.; Crafford, K.; Suliman, F.; Govender, N. (African Journal for Physical, Health Education, Recreation and Dance, 2014)
The aim of this study was to investigate the effects of electrical muscle stimulation (EMS) training on hamstring muscle strength. The study utilised a quantitative experimental research design. The intervention was assessed using a Humac Norm 7000 Dynamometer. A Chattanooga Intelect Mobile Combo muscle stimulator was used for the 4-week EMS training based on the 10-50-10 or "Russian Protocol". Descriptive statistics were performed and pre- to post-test changes were analized using dependent t-tests. Statistical significance was set at p=0.05. Following 4-weeks` EMS training there were statistically significant increases in both the PTQ and work performed during concentric isokinetic knee flexion at 60°/s. There was also a 21.4% increase in the H/Q ratio following the EMS training. Considering the present results and previous research conducted, both the quadriceps and hamstring muscles groups seem to be responsive to EMS strength training.